2008
DOI: 10.1007/s00128-008-9427-4
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Determination of Omethoate and Dichlorvos by Capillary Electrophoresis

Abstract: A capillary electrophoresis method has been developed for the analysis of omethoate and dichlorvos. Response surface methodology (RSM) was used to optimize the separate conditions for simultaneous detection of omethoate and dichlorvos. The results indicated that the optimal conditions for omethoate and dichlorvos determination were; pH 7.64, SDS concentration 67.5 mM, separation voltage 19.0 KV. Quantitative linear ranges were 1.0-300 microg/mL for omethoate and dichlorvos with correlation of 0.9967 and 0.9965… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 15 publications
1
2
0
Order By: Relevance
“…The detection limit values were found to be 2.47 Â 10 À10 M and 3.28 Â 10 À10 M for OMT and DCV respectively, which compare well with the detection limits obtained previously. [36][37][38] Thus, these results clearly indicate that the proposed electrochemical method of analysis is reliable for the determination of the individual pesticides (Fig. 8).…”
Section: Calibration Curves and Limits Of Detectionsupporting
confidence: 53%
See 1 more Smart Citation
“…The detection limit values were found to be 2.47 Â 10 À10 M and 3.28 Â 10 À10 M for OMT and DCV respectively, which compare well with the detection limits obtained previously. [36][37][38] Thus, these results clearly indicate that the proposed electrochemical method of analysis is reliable for the determination of the individual pesticides (Fig. 8).…”
Section: Calibration Curves and Limits Of Detectionsupporting
confidence: 53%
“…37 Yugui Tao et al reported on the simultaneous determination of OMT and DCV by capillary electrophoresis. 38 Nevertheless, to the best of our knowledge, there is no electroanalytical report concerning the simultaneous determination of OMT and DCV using a palladium and graphene nanocomposite modied glassy carbon electrode.…”
Section: Introductionmentioning
confidence: 99%
“…For detection of dimethoate and omethoate in soil and vegetables, capillary electrophoresis with MS detection after ionization by inductively coupled plasma (CE-ICP-MS) or UV-detection (CE-UV) has been rarely used [19,20]. In contrast, residues of both pesticides in different specimens (olive oil, olives, juice, urine and plasma) have often been quantified by more traditional gas chromatographic (GC) separation coupled to diverse detection techniques, e.g.…”
mentioning
confidence: 98%